A Dynamic Multivariate Causality Analysis of Energy–Growth Nexus Using ARDL Approach: A Malaysian Energy Policy Perspective - Khan, Habib Nawaz; Alrasheedi, Melfi; Shahzada, Gulap (Frontiers in Energy Research, 2021)
Abstract. This study analyzes a dynamic long and short-run causal nexus between energy consumption and economic growth in the presence of capital, labour, and urbanization over the time 1971 – 2014, in Malaysia. The stationarity issue was tested using Augmented Dickey Fuller (ADF), Kwiatkoski –Phillips-Schdmidt-Shin (KPSS), and Ng-Perron tests. However, dynamic long-run co-integration relation between variables was checked through the ARDL technique. Unrestricted Vector Error Correction Model (MUVECM) was used to estimate the short and long-run dynamic relation between the parameters and the Engle-Granger method for causality analysis. Statistical analysis confirmed that all variables were I(1) except labour I(0) and none of the variable I(2). Energy consumption and capital significantly impacted economic growth in a positive direction. However, labour and urbanization impacts were mixed. The Granger causality analysis confirmed mixed results in the short-run and the long-run. Moreover, estimated results confirmed a feedback hypothesis between income and capital in the short-term and long run. The short-run and long-run causal effects of the labour force on economic growth were confirmed. This study provides important insights to policymakers and energy economists. Prudent energy conservation policies and economically improved measures would be of great help. However, demand-side management-based policies would have no adverse effect on the economic performance of Malaysia.